التدريب على متطلبات القياس والتحليل والتحسين بنظام أدارة الجودة وأثره على تطوير أداء العاملين في وزارة التربية والتعليم بسلطنة عمان - Ali Muhamed Khalfan Aldarmaki
The study examined the training on the requirement for measurement, analysis and improvement in Quality Management System and its impact on advancement of employees’ performance in the Ministry of Education of the Sultanate of Oman. Moreover, the study aimed at measuring the impact of training on the performance of employees in the counterparts of Directorate General of Planning and Quality Control as well as the counterparts of the Directorate General of Administrative Affairs in the Educational directorates in the governorates of Ministry of Education of the Sultanate of Oman according to the requirements of measurement, analysis and improvement in quality management system by specification of the ISO 9001/2008 standard under the bands of monitoring and measurement, control of non-conforming product, data analysis and improvement. Thus, the researcher used the analytical descriptive method by describing and analyzing the impact of the training on the performance of the employees, using a questionnaire applied to the sample of 251 individuals. They were randomly selected, and they comprised of human resources employees in the counterparts of the Directorate General for Planning and Quality Control as well as the counterparts of the Directorate General for Administrative Affairs in the educational directorates of the governorates in the Ministry of Education in the Sultanate of Oman. Moreover, the researcher utilized Statistical Package for the Social Science (SPSS) for data analysis while using arithmetic averages, standard deviation, T-Test, mono-variance analysis, Pearson correlation coefficient, Alpha Cronbach stability coefficient, and oral test for dimensional comparisons. The study found that the level of training in the development of the performance of the workers came to a large extent in all the requirements of measurement, analysis and improvement of the quality management system. Further, the results showed a statistically significant impact of training on all requirements. The study also found that there were no statistically significant differences due to gender in all requirements differences. While there are statistically significant due to the variable functional level in all requirements of differences, as well as in terms of training method, it has been noted that there were statistically significant differences between the training methods in all requirements differences. This study was carried out with several recommendations. The most important of which is the adoption of the training kit in the current study as a training mechanism that seeks to develop the performance of the employees, and to disseminate the training kit model which is presented to all the divisions in the ministry, and focus on electronic training as it is the fastest and easiest tool to get the training material for the employees in conformity to the provisions of the other standards, and subject all employees to the training programs in order to enable them to upgrade their performance.